PERBEDAAN PENILAIAN ANTARA PENGUNJUNG HARI KERJA DAN AKHIR PEKAN TERHADAP ATRIBUT OBJEK WISATA KAMPOENG VIETNAM DI KOTA BANDAR LAMPUNG - Gumay, Muhammad Adhitya; Hudoyo, Agus; Saleh, Yuliana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This research aims to analyze the differences between weekday and weekend visitors to assess and rank the importance attributes of the Kampoeng Vietnam tourist attraction, as well as to identify attributes that need to be improved, and attributes that need maintenance to increase performance. This research used a survey method by interviewing 35 visitors of Kampoeng Vietnam in a weekday, and 35 visitors in the weekend   There are 16 attributes included in the questionnaire. The sample selection was conducted by using probability sampling methods. Data analysis used was Mann-Whitney test and Importance Performance Analysis (IPA). The results of the Mann-Whitney test indicate that there is a significant difference between the assessments of weekday visitors and weekend visitors regarding the importance level of the attributes of amusement rides, accommodations, and the tranquility of tourists. The ranking assessments of weekday visitor indicate that the attributes of photo spots, scenery, and air quality are in the highest rate; while the weekend visitor rank assessments show that the attributes of price, photo spots, and play attractions are received the highest rankings. Meanwhile, the result of IPA indicated that there are six attributes with different levels of importance and performance between weekday visitors and weekend visitors. Furthermore, the combined results of the IPA analysis for weekday visitors and the IPA for weekend visitors conclude that there are five attributes that need improvement and eight attributes that should maintain their performance. Keywords: attribute, IPA, weekday, weekend